2021
DOI: 10.29271/jcpsp.2021.06.633
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Rectus Sheath Hematoma

Abstract: Objective: To evaluate the risk factors for developing rectus sheath hematoma (RSH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…An observational study of 61 patients showed that 91.8% (56) suffered from at least one chronic disease, whereas 77% were currently on anticoagulation therapy [ 6 ]. It was determined that patients who took acetylsalicylic acid had larger RSH sizes when compared to those who took other anticoagulants [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of 61 patients showed that 91.8% (56) suffered from at least one chronic disease, whereas 77% were currently on anticoagulation therapy [ 6 ]. It was determined that patients who took acetylsalicylic acid had larger RSH sizes when compared to those who took other anticoagulants [ 7 ].…”
Section: Discussionmentioning
confidence: 99%